Structure and expression of an alpha-tubulin gene of Physarum polycephalum. - Walden, P; Monteiro, M; Gull, K; Cox, R (1989)
Fragments of Physarum polycephalum DNA generated by partial digestion with Sau3A were cloned into phage-lambda EMBL4. A recombinant (phage-lambda E alpha Tu) containing an alpha-tubulin (E alpha-tubulin) gene was isolated. The E alpha-tubulin gene is part of the alt B locus. The gene was sequenced and was found to contain seven intervening sequences. The alpha-tubulin isotype (E alpha-tubulin) encoded by the gene has a methionine residue at the C-terminus. The E alpha-tubulin gene has much in common with the N alpha-tubulin gene cloned into phage-lambda NM1149 [M. J. Monteiro and R. A. Cox (1987) J. Mol. Biol. 193, 427-438]. However, the gene products E alpha-tubulin and N alpha-tubulin differ in amino acid sequence near to the C-terminus. E-peptide (corresponding to amino acids 440-448 of E alpha-tubulin) and N-peptide (corresponding to amino acids 437-445 of N alpha-tubulin) were synthesised and used to raise antibodies (E-antibodies and N-antibodies). The antibodies were used to show that on two-dimensional gel electrophoresis N alpha-tubulin travels to the alpha 1 position and E alpha-tubulin moves to the alpha 2 position. Gene-specific DNA probes were used to show that transcripts of the E alpha-tubulin gene were present in the plasmodial but not in the amoebal phase of the life cycle. The E- and N-antibodies detected E alpha- and N alpha-tubulins in plasmodia but not in amoebae, confirming that the expression of the E alpha- and N alpha-tubulin genes is regulated during development. E alpha- and N alpha-tubulin were shown to be components of spindle microtubules by indirect immunofluorescence microscopy.